Injection characteristics of near critical and supercritical kerosene into quiescent atmospheric environment. (1st January 2019) - Gao, Wei; Lin, Yuzhen; Hui, Xin; Zhang, Chi; Xu, Quanhong
Abstract: The injection of RP-3 aviation kerosene at near and above critical conditions into a quiescent atmospheric environment is experimentally investigated with special emphasis on the effects of injection temperature and pressure on the jet characteristics of shock structure and phase transition. Visualization of the near-field shock/jet structure is performed using Schlieren imaging. Results show that fuel condensation occurs when supercritical RP-3 is injected at near critical temperature. At the supercritical injection conditions investigated, ideal-gas-like expansion and internal shock structures are observed. A RP-3 surrogate is used to determine the thermodynamic phase diagram to reveal the phase transition during the injection processes. The characteristics of the Mach disk are further presented and discussed. It is found that the location and size of the Mach disk as well as jet expansion angle increase with increasing injection pressure. Furthermore, specific heat ratios and compressibility factors of RP-3 surrogate and N2 are evaluated to analyze their differences in Mach disk diameter and jet expansion angle; it is shown that the compressibility factor is the primary factor that deviates the jet structure of RP-3 from that of ideal-gas N2 .